Análise do discurso e ciência da Informação: aportes teóricos para organização e representação da Informação - Moraes, João Batista Ernesto [UNESP]; Lima, Larissa Mello [UNESP]; Caprioli, Mariana Silva [UNESP] (My University, 2016)
Is intended to bring a brief overview of the conceptual and theoretical discourse analysis of the French Discourse Analysis as a viable methodology to be used in theoretical studies for representation and information organization within the frame of Information Science. For this, selected authors as Foucault (1985; 2010), Orlandi (1999) and Mazière (2007) were reviewed, who offer fundamental discussions on the French Discourse Analysis. The second step was to discuss the issue of the interdisciplinarity nature of Information Science in order to fortify the bases for the constitution of the relationship between the French Discourse Analysis and Information Science.
Discourse analysis and Information Science: Theoretical contributions to information organization and representation
Keywords: Discourse analysis; Foucault; French school of discourse analysis; Information science; Interdisciplinarity; Michel; Subject indexing